Current trends in the creation of cell-free allo- and xenotissues for reconstruction of heart structures - S. I. Babenko; R. M. Muratov; M. N. Sorcomov (Вестник трансплантологии и искусственных органов)
Tissue engineering has significant potential for solving the problems of durability of biological tissues when used in cardiac and vascular reconstructive surgery. A decellularization technology has been proposed for obtaining a biomaterial, morphologically and functionally similar to the damaged human heart tissue. This review discusses various aspects and models of biological tissue decellularization, including the modern technology of using supercritical carbon dioxide as the most eco-friendly and promising method.